2019
DOI: 10.1055/a-0982-2862
|View full text |Cite
|
Sign up to set email alerts
|

Role of EUS-FNA for gallbladder mass lesions with biliary obstruction: a large single-center experience

Abstract: Background and study aims  Although endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) is an established modality for pathological sampling of pancreatic and biliary lesions, limited data are available on the diagnostic value of EUS-FNA for evaluation of gallbladder mass lesions, a common cause of obstructive jaundice. We aimed to evaluate the usefulness of EUS-FNA for diagnosis of gallbladder mass lesions presenting with biliary obstruction. Patients and methods  This study was a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Among them, one article was excluded due to lack of histological data on the patients, two more were excluded due to lack of clear clarification of how the final diagnosis was confirmed for every patient and finally, one article was excluded because it included only six patients. Ultimately, six articles [14][15][16][17][18][19] were selected for inclusion in the qualitive and quantitative analysis (Figure 1). how the final diagnosis was confirmed for every patient and finally, one article was excluded because it included only six patients.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, one article was excluded due to lack of histological data on the patients, two more were excluded due to lack of clear clarification of how the final diagnosis was confirmed for every patient and finally, one article was excluded because it included only six patients. Ultimately, six articles [14][15][16][17][18][19] were selected for inclusion in the qualitive and quantitative analysis (Figure 1). how the final diagnosis was confirmed for every patient and finally, one article was excluded because it included only six patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one meta-analysis with 284 patients who underwent EUS-biopsy for biliary and gallbladder masses did not observe any complications of seeding, bile leak, or cholangitis [ 28 ]. Similarly, in another study of 101 patients with gallbladder masses who underwent EUS-FNA, there were no complications of procedure-related cholangitis or bile leak in any patient [ 37 ]. However, Johnson et al reported that percutaneous biopsy for pancreatic cancer also did not significantly increase positive peritoneal washings or peritoneal failure rate [ 38 ].…”
Section: Diagnostic Testsmentioning
confidence: 88%
“…This technique poses the risk of perforating the gallbladder duct with the guidewire. In contrast, if a gallbladder lesion can be visualized as a tumor by EUS, a pathological diagnosis can be established using EUS-FNA [29].…”
Section: Eus-fna Of the Gallbladdermentioning
confidence: 99%